First report of Rhodnius stali Lent, Jurberg & Galvão, 1993 (Hemiptera: Reduviidae: Triatominae), vector of Trypanosoma cruzi (TcI) and Trypanosoma rangeli (TrA), in Rondônia, Southwestern Brazilian Amazonia - Rodrigues Menezes, André Luiz [UNESP]; Ribeiro, Mariane Albuquerque Lima [UNESP]; Nascimento da Cruz, Lucas; de Carvalho, Elaine Oliveira Costa; Oliveira, Jader de; Geraldes Teixeira, Marta Maria; Aristeu da Rosa, João [UNESP] (My University, 2023)
Triatomines are hematophagous insects of epidemiological importance as they are vectors of Chagas disease. The first report of Rhodnius stali Lent, Jurberg & Galvão, 1993 in Rondônia, Brazil, is described. The insects were captured on palm trees of the genus Oenocarpus sp. Two adult male specimens of R. stali were identified and were found to be infected with Trypanosoma cruzi and Trypanosoma rangeli. The confirmation of this Rhodnius species in Rondônia increases the number of triatomines from nine to ten species in this state.
Keywords: Entomological surveillance; Kissing bugs; New records; Western Amazon